1978
DOI: 10.1161/01.res.42.2.271
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of the acid mucopolysaccharide composition of rheumatic and normal heart valves in man.

Abstract: SUMMARY The nature and relative proportions of acid mucopolysacharides (AMPS) in mitral valves of normal individuals and individuals with rheumatic valvular disease were compared. The total AMPS content of valves from rheumatic patients under 21 years of age is significantly higher than that from older rheumatic patients and higher than that from age-matched normal controls. The major AMPS components of both normal and rheumatic valvular tissue are hyaluronic acid, chondroitin sulfate A/C, and chondroitin sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

1980
1980
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…Earlier studies on the AMPS content of mitral valvular tissue obtained from normal and rheumatic individuals revealed that valvular tissue from young rheumatic individuals contained significantly more AMPS than age-matched normal controls (Baig et al, 1978). The results of the studies reported here did not reveal similar difference in the AMPS content of skin fibroblasts of normal and rheumatic individuals.…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations
“…Earlier studies on the AMPS content of mitral valvular tissue obtained from normal and rheumatic individuals revealed that valvular tissue from young rheumatic individuals contained significantly more AMPS than age-matched normal controls (Baig et al, 1978). The results of the studies reported here did not reveal similar difference in the AMPS content of skin fibroblasts of normal and rheumatic individuals.…”
Section: Discussioncontrasting
confidence: 79%
“…Circ Res 46: 651-659, 1980 THE SPECIFIC lesions of acute rheumatic fever which occur in the heart, joints, and, to a lesser degree, in other organs are swelling and hyalinization of the collagenous ground substance of the fibrous tissue (Klinge, 1933). The susceptibility of certain individuals to this complication of group A streptococcal infection has raised the possibility of an inherent abnormality in the reaction of the tissue of rheumatic individuals to injury (Baig et al, 1978). Because acid mucopolysaccharides (AMPS) are primary components of the ground substance of valvular tissue, we undertook in a previous study to determine whether differences were present in the AMPS composition of rheumatic and non-rheumatic valvular tissue (Baig et al, 1978).…”
Section: Metabolism Of Complex Carbohydrates By Fibroblasts From Rheumentioning
confidence: 99%
See 2 more Smart Citations
“…These studies include one in which we showed that the calcification of Glut fixed cusps in the rat subdermal model was accompanied by a marked decrease in GAG content and a concomitant increase in GAGdegrading enzyme activities [11]. Lower quantities of GAGs have also been reported in calcified natural valves [43], as well as in clinically failed, calcified BHVs [15]. Using the rat subdermal model it has also previously been demonstrated that the extraction of GAGs before Glut fixation stimulated the calcification of bovine pericardium [44] and conversely, the covalent immobilization of hyaluronic acid mitigated pericardial calcification [45].…”
Section: Effects Of Gag Removal On Calcificationmentioning
confidence: 99%